Metal accumulation patterns in Pittsburgh, PA (United States) green infrastructure soils: road connections and legacy soil inputs - Brewster, Brandon M.; Bain, Daniel J. (Frontiers in Environmental Science, 2023)
Aging water infrastructure renewal in urban areas creates opportunities to systematically implement green infrastructure (GI) systems. However, historical soil contamination from gasoline lead additives, steel manufacturing by-products, and other historical industry raise the potential that novel GI drainage patterns and geochemical environments may mobilize these legacy pollutants to green infrastructure sites previously isolated from most hydrologic flows. Characterization of GI soil chemistries across GI type to build on previous observations in other cites/regions is fundamental to accurate assessments of these emerging management scenarios and the resultant risk of increased metal exposures in downstream environments. In particular, clarification of ecosystem services this metal sequestration may provide are vital to comprehensive assessment of green infrastructure function. During 2021, soil metal chemistry, specifically, As, Cr, Cu, Fe, Mn, Ni, Pb, V, and Zn was measured at a high spatial resolution in six Pittsburgh (Pennsylvania, United States) GI installations using a portable X-ray Fluorescence Spectrometer. Patterns of trace metal accumulation were identified in these installations and evaluated as a function of site age and GI connection to road systems. Trace metals including chromium, copper, manganese, and zinc all seem to be accumulating at roadside edges. Remobilization of historically contaminated soils also seems to be a potential mechanism for transporting legacy trace metal contamination, particularly lead, into GI systems. However, metals were not clearly accumulating in installations less connected to road inputs. These findings are consistent with literature reports of trace metal transport to GI systems and reconfirm that clarification of these processes is fundamental to effective stormwater planning and management.